A survey on the rotifer (Rotifera) fauna of the Yucatan Peninsula (Mexico) - Sarma, S. S.S.; Elías-Gutiérrez, Manuel (Revista de Biología Tropical, 1999)
Taxonomic studies on the freshwater rotífers were conducted on samples collected from 12 localities in the south-central part of Quintana Roo State (Yucatan Península, Mexico) during 1997. The water bodies sampled ranged from small cenotes (carstic deep circular sinkholes) to temporary and permanent lagoons. Data on selected physical and cheroical variables of tbe waterbodies were also obtained. We recorded 102 rotifer species of which 15 are new to the fauna of Mexico. These are: Eosphora anfhadis, Eosphoia carogaensis, Lecane aeganea, Lecane grandis, Lecane haliclysta, Lecane margarethae, Lecane rugosa, Lecane sibina. Lecane spinulifera, Lecane uenoi, Lepadella donneri, Lepadella heterostyla, Macrochaetus longipes, Proales daphnicola, and Ptygura tacita. In this study, we present illustrations of all new records and comments on selected taxa from a zoogeographical point of view.